2020
DOI: 10.1002/iub.2238
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metabolomic analysis of intestinal ischemia–reperfusion injury in rats

Abstract: Intestinal ischemia–reperfusion injury (IIR) is a life‐threatening abdominal emergency. Compared to traditional steady‐state works, we profiled the blood of rats over 72 hr (15 time points) and examined dynamic changes in molecular pathways during IIR. Using a series of methods designed for dynamic datasets analysis (batch effects corrections, metabolomics data reduction, and different features selection), we identified 39 significant different metabolites and discovered the trends of these molecules. Four mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Many physicians envision a future where MP is used to improve the function of each donor liver to achieve maximal graft utilization and minimize discard rates [ 10 , 11 ], and one potential method to improve graft function is targeting metabolism. While numerous studies have demonstrated potential metabolic targets in the liver, renal, and intestinal IRI response [ 12 , 13 , 14 , 15 , 16 ], few studies have examined the metabolic changes that occur in the human liver during transplantation [ 12 , 17 , 18 , 19 , 20 ] and fewer still during ex situ machine perfusion [ 4 , 21 ]. This is a critical area of research since the machine perfusion platform is the only setting for liver-specific adjunct therapies prior to transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Many physicians envision a future where MP is used to improve the function of each donor liver to achieve maximal graft utilization and minimize discard rates [ 10 , 11 ], and one potential method to improve graft function is targeting metabolism. While numerous studies have demonstrated potential metabolic targets in the liver, renal, and intestinal IRI response [ 12 , 13 , 14 , 15 , 16 ], few studies have examined the metabolic changes that occur in the human liver during transplantation [ 12 , 17 , 18 , 19 , 20 ] and fewer still during ex situ machine perfusion [ 4 , 21 ]. This is a critical area of research since the machine perfusion platform is the only setting for liver-specific adjunct therapies prior to transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma was prepared with a two-step derivatization procedure, that is, alkylation and silylation, according to previous reports with a few modifications ( 21 , 22 ). Briefly speaking, a 10 µL aliquot of plasma was thoroughly vortexed with ten times methanol followed by centrifuged at 18047g at 4°C for 10 min in two cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies reported the use of metabolomics technologies to study intestinal IR injury [37][38][39][40][41], of which two also applied metagenomics [40,41]. The earliest investigation into metabolomics in the context of intestinal IR injury dates back to 2010.…”
Section: Metabolomics and Metagenomicsmentioning
confidence: 99%
“…Conversely, the metabolites in the biosynthesis of unsaturated fatty acids pathway exhibited an opposite trend, with levels of oleic acid, palmitic acid, arachidonic acid, linoleic acid, and stearic acid reaching its nadir at 2 h of reperfusion. Other imperative pathways that were regulated during IR included amino acid biosynthesis, 2‐oxocarboxylic acid metabolism, arginine‐related metabolism, and glutathione metabolism [39].…”
Section: Omics In In Vivo Mouse and Rat Intestinal Ir Modelsmentioning
confidence: 99%